La fête et la lutte : Religion et mouvements autochtones dans la Sierra Nororiental de Puebla (Mexique) - Beaucage, Pierre; Olguín, Leonardo Durán; Pasquel, Ignacio Rivadeneyra; Ramírez, Claudia Marina Olvera (Anthropologica, 2017)
The analysis of contemporary protest movements of the Nahuas and Totonaques of Puebla’s Nororiental Sierra (Mexico) leads us to formulate the hypothesis that the religious and the political are closely intertwined. The strongest link concerns the Theology of Liberation, which has contributed to a revalorisation of Indigenous identities since the 1960s legitimated social struggles. A much deeper link with religion appears when we analyse Amerindian cosmology, which is periodically actualized in large community rituals.